VARNIAI BOOKSTORE ADVERTISEMENT OF 1853 - PETREIKIS, TOMAS (Knygotyra, 2011)
Vilniaus universiteto Knygotyros ir dokumentotyros institutas Universiteto g. 3, LT-01513 Vilnius, Lietuva El. paštas: petreikist@gmail.com